ANAL1SIS BEBAN PENCEMARAN, KAPASITAS ASIMILASI DAN TINGKAT PENCEMARAN DALAM UPAYA PENGENDALIAN PENCEMARAN PERAIRAN DANAU MANINJAU - Marganof, Marganof; Darusman, Latifah K; Riani, Fain; Pramudya, Bambang (Fakultas Perikanan dan Kelautan Universitas Riau, 2007)
Water quality in Maninjau Lake has been thereatened by organic and inorganicmatters that are flown into the lake. The pollution sources arc many activitiesaround the lake such as residential area, husbandry, agriculture, an fish culture onthe lake (floating net cage). These activities result in huge pollution laods and thetrends are predicted to increase. Understending on the pollution loads, polluitonsources and asssimilativc capacity are important in formulating pollution controltechniques in lake waters. The objectives of the research was to determine level ofpollution waters of Maninjau Lake. The results of this research showed thatpollution load parameter susch as Total Suspended Solid (TSS), ChemicalOxygen Demand (COD), Biochemical Oxygen Demand (BOD) and TotalPhosphorus were very high. All parameters of pollution loads have ciceded itsasssimilative capacity. The level of pollution in the study site is classified asmedium category.